Pengaruh Pendapatan, Literasi Keuangan, dan Herding Behavior Terhadap Keputusan Investasi Mahasiswa dan Pekerja di Provinsi Lampung - Yustia Sabela Yuliani; Ratna Septiyanti (BADAN PENERBIT STIEPARI PRESS, 2025)
Investment is currently increasingly in demand by various levels of society, including the younger generation consisting of students and those who have entered the workforce. This study aims to analyze the effect of income, financial literacy, and herding behavior on investment decisions of students and workers in Lampung Province. This study uses a quantitative approach with a survey method. The sample in this study was 100 respondents consisting of students and workers, who were selected using a purposive sampling technique. The data analysis technique used was multiple linear regression analysis with the help of the SPSS version 26 program. The results of the study showed that the income variable had a positive and significant effect on investment decisions. Financial literacy also had a positive and significant effect on investment decisions. In addition, herding behavior also had a positive and significant effect on investment decisions. Thus, these three variables simultaneously have a significant influence in determining investment decisions of students and workers in Lampung Province. In addition, based on the determination coefficient test, the Adjusted R Square value was obtained at 0.521 or 52.1%, which means that the variables of income, financial literacy, and herding behavior are able to explain 52.1% of the variation in investment decisions, while the remaining 47.9% is explained by other variables outside this research model.